Evaluation of the economic impact of the application of strategies for development in the rural area - Quispe, Renán (2019)
With a macroeconomic context favored by a GDP growth of 5%, growth in investment and exports, it has been seen that the improvement in access to education, the growth in road infrastructure with greater intensity as of 2010. The action of the social actors of the state resulted in an increase in income and real spending per capita of households, with the final consequence of poverty reduction in rural areas. The gross agricultural product as an indicator of economic activity in the rural area has had an increasing behavior based on the greater area harvested, the increase in agricultural labor supply and, to a lesser degree, the importation of capital goods. The measurement of the impact in a transversal way has been made from the evaluation of the Juntos program for the years 2012 - 2013 from a panel sample. It was concluded that the program has improved the life level of the rural population being driven by education.